2021
DOI: 10.1161/strokeaha.120.033070
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Month Outcomes of the AFFINITY Trial of Fluoxetine for Functional Recovery After Acute Stroke: AFFINITY Trial Steering Committee on Behalf of the AFFINITY Trial Collaboration

Abstract: Background and Purpose: The AFFINITY trial (Assessment of Fluoxetine in Stroke Recovery) reported that oral fluoxetine 20 mg daily for 6 months after acute stroke did not improve functional outcome and increased the risk of falls, bone fractures, and seizures. After trial medication was ceased at 6 months, survivors were followed to 12 months post-randomization. This preplanned secondary analysis aimed to determine any sustained or delayed effects of fluoxetine at 12 months post-randomization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It did show a decreased occurrence of depression in the fluoxetine group but an increased risk of bone fractures 6 . The AFFINITY (Assessment of fluoxetine in stroke recovery) trial showed similar results, as did another randomized controlled trial by the name of EFFECTS (Efficacy oF Fluoxetine – a randomisEed Controlled Trial in Stroke) 7 , 8 . Another phase 2 trial by the name of FLOW (fluoxetine opens window to improve motor recovery after stroke) is currently ongoing.…”
Section: Drugs Have Been Shown To Enhance Neuroplasticitymentioning
confidence: 63%
“…It did show a decreased occurrence of depression in the fluoxetine group but an increased risk of bone fractures 6 . The AFFINITY (Assessment of fluoxetine in stroke recovery) trial showed similar results, as did another randomized controlled trial by the name of EFFECTS (Efficacy oF Fluoxetine – a randomisEed Controlled Trial in Stroke) 7 , 8 . Another phase 2 trial by the name of FLOW (fluoxetine opens window to improve motor recovery after stroke) is currently ongoing.…”
Section: Drugs Have Been Shown To Enhance Neuroplasticitymentioning
confidence: 63%
“…The few studies that evaluated cognitive outcomes after acute stroke treatments suggest that intravenous thrombolysis and mechanical thrombectomy improve cognitive outcomes (compared with no treatment) but that these benefits are strongly associated with functional outcome. [140][141][142] Systematic reviews of dopamine agonists 143 and selective serotonin reuptake inhibitors [144][145][146] show no consistent beneficial effects on cognition after stroke. Individual small clinical trials have reported various pharmaceutical agents that may have a potential benefit on global cognition: neurotrophics (Cortexin), 147 peptides such as Cerebrolysin 148 and relaxin, 149 citicoline (cytidine-5ʹ-diphosphocholine), 150 and nitrates (glyceryl trinitrate).…”
Section: Medical and Pharmacological Treatmentsmentioning
confidence: 99%
“…However, a subsequent Cochrane systematic review, including 52 randomized trials, challenged these results, given the methodological limitations and heterogeneity of studies [102]. Therefore, three additional large randomized controlled clinical trials (AFFINITY: Assessment of Fluoxetine in Stroke Recovery, FOCUS: Fluoxetine or Control Under Supervision trials, and EFFECTS: Efficacy of Fluoxetine-a Randomised Controlled Trial in Stroke) were conducted and they did not show functional improvement at 6 months, measured by a modified Rankin Scale (mRS) [103][104][105]. The main issues with these trials include the heterogeneous study population with mainly mild stroke patients, which might decrease the sensitivity to detect group differences.…”
Section: Selective Serotonin Reuptake Inhibitors (Ssris)mentioning
confidence: 99%